Miscellaneous optical solitons in magneto-optic waveguides associated to the influence of the cross-phase modulation in instability spectra - Abbagari, Souleymanou; Alphonse, Houwe; Mukam, Serge P.; İnç, Mustafa; Serge, Doka Y.; Bouetou, Thomas B. (Iop Publishing Ltd, 2021)
By employing the traveling-wave hypothesis to the coupled nonlinear Schrodinger equation (CNLSE), the constraint relation on metamaterials parameters and the auxiliary equation have been recovered successfully. Conjecturing the values of the coefficients of the auxiliary equation, a diversity of solutions have been constructed while respecting the conditions of existence of these solutions. By choosing adequate parameters, it is obtained W-shape bright, dark, kink, anti-kink like optical solitons for the CNLSE which controls waves in magneto-optic waveguides in the presence of cross-phase modulation (XMP). To deal with the influence of the XMP to Modulation Instability (MI), the linearization technique was adopted and the continuous wave (CW) solutions were used to obtaining the dispersion relation as well as the associated MI gain spectrum. The study of the MI gain spectrum have been done in the normal and anomalous dispersive regimes associated with zero-birefringence, linear-birefringence and circular birefringence. The MI gain spectrum curves illustrating the miscellaneous of optical solitons in the magneto-optic waveguides were obtained. It is noted that these results sufficiently illustrate the dynamic of the nonlinear optic fibers through the 3D and 2D spatiotemporal plot evolutions.
Keywords: optical solitons; magneto-optic waveguides; influence of the cross-phase modulation